The Understanding Ability of Exercises of Higher Order Thinking Skill-Based Anecdote Text in 10th Grade Students of Senior High School 1 Tanjung Tiram - Cica Elida Hanum Matondang; Wisman Hadi; Malan Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of this study is to know the understanding ability of exercises of higher order thinking skill-based anecdote text in 10th grade students of senior high school 1 Tanjung Tiram. This study was conducted in the odd semester of the 2018/2019 academic year which was planned starting from the collection of knowledge data to the writing as a whole. The subjects of this study were 10th grade students of Senior High School 1 Tanjung Tiram as many as 30 students. The object carried out in this study is a guide to higher order thinking skill (HOTS)-based knowledge instruments. The result shows that the understanding ability of exercises of higher order thinking skill-based anecdote text the students get an average score of 60.56% in the "sufficient" category. Thus, it can be stated that a high level of knowledge instrument on students of senior high school 1 Tanjung Tiram with sufficient quality.